The beam test of anticoincidence scintillation detector prototype with SiPM readout and perspectives of GRBs studies for space-based gamma-ray telescope GAMMA-400. (November 2019) - Arkhangelskiy, A I; Galper, A M; Arkhangelskaja, I V; Bakaldin, A V; Chasovikov, E N; Chernysheva, I V; Dalkarov, O D; Egorov, A E; Gusakov, Yu V; Kheymits, M D; Leonov, A A; Pappe, N Yu; et al.
Abstract: The GAMMA-400 project will be the new generation of satellite gamma-observatory. GAMMA-400 space-based gamma-ray telescope represents the core of the scientific complex intended to perform a search for signatures of dark matter in the cosmic gamma-emission, measurements of diffuse gamma-emission characteristics, investigation of extended and point gamma-ray sources, studying of high energy component of gamma-ray bursts and solar flares emission. Four fast plastic sub-detectors of the gamma-ray telescope are included in fast trigger logic in the main telescope aperture. This aperture expected angular and energy resolution are ∼0.01° and ∼1-2% respectively for gammas with the energy >100 GeV and electron/protons rejection factor ∼5-10 5 . Prototype of anticoincidence detector based on long BC-408 scintillators with SiPM readout for gamma-ray telescope was tested on a 300 MeV secondary positron beam of synchrotron C-25P «PAKHRA» of Lebedev Physical Institute in Russia. The measurement setup, design concepts for the prototype detector and chosen solutions together with some test results are discussed. Two other apertures (additional and lateral) allow analyzing transient events not required precision angular resolution, for examples, GRBs and solar flares. Similar plastics sub-detectors included in their fast trigger logic. Using of all three apertures allows making more effective observations of GRBs (better signal to noise ratio), more detailed study of its high energy afterglow due long term measurements (because of high apogee orbit provides low background variations with time) and detailed analysis of the sources luminosity variability (spectral, angular and temporal).